PERAN MODERASI TEKNOLOGI INFORMASI PADA PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI KANTOR DESA BAKTISERAGA - Prastiwi, Ni Luh Putu Eka Yudi; Mahayuni, Gusti Putu Sri (Universitas Panji Sakti, 2023)
This research was conducted at the Baktiseraga Village Office which aims to determine Competency Development in Improving Employee Performance at the Baktiseraga Village Office. The sample used in this research was all 58 people from the Baktiseraga Village Office. The type of data used is quantitative data, primary and secondary data sources were collected using documentation and questionnaire techniques. The data analysis technique used was multiple linear regression analysis assisted by SPSS version 25 software. From the results obtained, it is known that the question items are valid and reliable. Furthermore, from the classical assumption test as a whole is fulfilled so that the data obtained is feasible for regression analysis after testing, the results of the model test, namely Analysis of the coefficient of determination, obtained the strength of the relationship between competency development variables, information technology, employee performance. The results of this study are competency has a significant positive effect on employee performance and the results of the study state that Information Technology is a quasi-moderating variable.